Treatment of wastewater from rubber processing using hydroxyapatite and lampang clay nanocomposite filters - Chankachang P. (2017)
© 2016 Trans Tech Publications, Switzerland. Nanocomposite filters were prepared by sintering of hydroxyapatite (HA) and Lampang clay composite nanopowder. 50 wt% amount of Lampang clay nanopowder are incorporated into HA nanopowder. The mixing powders are uniaxially compact and then sintering at 900°C-1050°C in air. The bending strength tests were performed and microstructure characterizations were carried out by scanning electron microscopy and mercury porosimetry analysis in order to determine the optimum sintering conditions. Filtration studies using optimized filter were performed for rubber wastewater. The results from this work clearly show that nanocomposite filter is an efficient and ecologically suited environmental technology for decontamination of the wastewater generated from rubber processing.